Effects of amine molecular structure on carbon nanotubes functionalization - Jimeno, A (2009)
Three amines with different molecular structure, triethylenetetramine (TETA) and two polyetheramines (Jeffamine D-230 and Jeffamine T-403) were employed to functionalize multi-walled carbon nanotubes (MWCNT) previously oxidized by acid treatment. The functionalized MWCNT were characterized by Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy, UV-vis spectroscopy and the surface modification was investigated by field emission scanning electron microscopy (FE-SEM). Thermogravimetric analysis (TGA) was employed to quantify the amount of amine groups anchored to MWCNTs. The results have shown that the efficiency of amine functionalization is in the order TETA > D-230 > T-403, thus showing that amine chemical structure and molecular weight are important parameters on functionalization of carbon nanotubes. Copyright © 2009 American Scientific Publishers.